A Report on Water, Energy and Food Relationship - Sajid, Mehmood; Muhammad, Imtiaz; Muhammad, Rizwan; Saqib, Bashir; Gutha, Yuvaraja; Sana, Ur Rehman; Waqas, Ahmed; Di-Yun, Chen (International Journal of Nutrition, 2019)
With the possibility of the Water-Energy-Food (WEF) Nexus since a long time back, overlooked interlinkages between WEF are getting the chance to be indisputable. Nonetheless, agriculture is responsible for quite a bit of fresh water over-use. Food production further effects the water and energy sectors through degradation of land, changes in overflow, disturbance of groundwater release, water quality, accessibility of water and land for different purposes. The responsibilities of this unparalleled issue include particular parts of the organization around the Nexus. While a couple of papers try to conceptualize the Nexus-Governance, this phenomenal report gives a rich combination of work for further WEF-Nexus ponders and integrative methodologies.
Keywords: Water; energy; food; nexus; degradation